Influence of post materials on the fracture resistance of endodontically treated teeth. (Mustansiria Dental Journal, 2018)
The bending stiffness of the post should have the ability to transfer and distributeforces and stresses in an endodontically treated tooth to prevent root fracture. The aimof this study was to evaluative the post materials on the fracture resistance ofendodontically treated teeth restored with three types of post materials. Thirtyextracted human mandibular premolars after root canal preparation and obturationwith gutta percha; the roots were divided into three groups according to the type ofpost material, group Fc restored with fiber post, group Sc restored with stainless steelpost and group Tc restored with titanium post. All teeth restored with compositerestorative material as core materials. Then all the teeth were subjected tocompressive load at 130o angle from the horizontal plan at a 5mm/min crossheadspeed until fracture. Results showed that there was a significant different betweengroups in term of fracture loads (P= 0.0301). Also the fracture loads of teeth restoredwith titanium post has highest mean fracture load (830N), whereas teeth restored withFiber post demonstrated the lowest mean fracture load (701.3N). This studyconcluded that the teeth restored with metallic post were more fracture resistant thanthose restored with fiber posts. But the combination of a fiber post and composite corehas the favorable mode of fracture that considered reparable, while consideredunfavorable when restored with metallic post.